Public relations : the profession and the practice - Lattimore, Dan (McGraw-Hill Higher Education, 2009)
Offers coverage of global markets, new technologies, and multiculturalism. Accompanied by a DVD with video interviews of leaders in the public relations field, this work explains the fundamental tools of public relations practice, providing an understanding of the trends within the field